Habitat shapes the gut microbiome diversity of Malayan tigers (Panthera tigris jacksoni) as revealed through metabarcoding 16S rRNA profiling - Millawati, Gani; Mohd Ridwan, Abd Rahman; Frankie Thomas, Sitam; ZUBAIDAH, KAMARUDIN; SITI SUZANA, SELAMAT; Nik Mohd Zamani, Awang; Kayal Vizi, Karuppannan; Badrul Munir, Md Zain (Springer Nature, 2024)
The gut microbiome refers to the microorganism community living within the digestive tract. The environment plays a crucial role in shaping the gut microbiome composition of animals. The gut microbiome influences the health and behavior of animals, including the critically endangered Malayan tiger (Panthera tigris jacksoni). However, the gut microbiome composition of Malayan tigers, especially those living in their natural habitats, remains poorly understood. To address this knowledge gap, we used next-generation sequencing DNA metabarcoding techniques to analyze the gut microbiome of wild Malayan tigers using fecal samples collected from their natural habitats and in captivity. Our aim was to determine the gut microbiota composition of the Malayan tiger, considering the different types of habitat environments. The results revealed a diverse microbial community within the gut microbiome of Malayan tigers. The prominent phyla that were observed included Firmicutes, Proteobacteria, Actinobacteriota, Fusobacteriota and Bacteroidota. Beta diversity analysis revealed significant differences in gut microbiome composition of Malayan tigers that inhabited oil palm plantations, in villages and protected areas. Diversity analysis also revealed significant difference in the gut microbiome between wild and captive Malayan tigers. However, the distinctions of gut microbiome between wild and captive alpha diversity did not yield significant differences. The differences in microbiome diversity resulted from the interplay of dietary intake and environmental factors. This information will facilitate the establishment of focused conservation approaches and enhance our understanding of the effect of microbiome composition on Malayan tiger health.